Sistem Informasi Penjualan Secara Online Studi Kasus Pada Mechin Petshop Yogyakarta - Supriyanta .; Ita Nurhayati - Universitas BSI PSDKU Yogyakarta (Indonesian Journal of Networking and Security (IJNS), 2018)
ABSTRACT: The system is a collection of elements that are interconnected with a particular purpose. Mechin Petshop is a system in the city of Yogyakarta that was formed with the aim of selling various kinds of pet food and accessories. Mechin Petshop still makes conventional sales. Mechin Petshop relies on how to sell by buying or renting a store, keeping and waiting until the buyer arrives. The disadvantage is the product marketing range, limited service time and profits, so that the business development and sales turnover are few. In the long run the design of web-based information systems needs to be made to help develop an online sales system in Mechin Petshop. The design of this information system uses two methods, namely data collection techniques with methods of interview, observation, literature study and documentation, for software development techniques with the waterfall method, namely software requirements analysis, design, program code creation and testing. The tools used are ERD, LRS and Navigation Structure. Testing websites using Black Box Testing. The website that has been created is expected to provide convenience to consumers to make transactions online 24 hours and from wherever they are, it is expected that consumers can see products, can make transactions at any time, services are more convenient and profits can increase. Keywords: Information, Mechin Petshop, Online Sales ABSTRAKSI : Sistem merupakan kumpulan elemen-elemen yang saling berhubungan dengan tujuan tertentu. Mechin Petshop adalah sebuah sistem di Kota Yogyakarta yang dibentuk dengan tujuan menjual berbagai macam makanan dan aksesoris hewan peliharaan. Mechin Petshop masih melakukan penjualan secara konvensional. Mechin Petshop mengandalkan cara penjualan dengan membeli atau menyewa sebuah toko, menjaga dan menunggu hingga pembeli datang. Kelemahannya adalah jangkauan pemasaran produk, waktu pelayanan dan keuntungan yang terbatas, sehingga perkembangan usaha dan omset penjualan sedikit. Dalam jangka panjang perancangan sistem informasi yang berbasis web perlu dibuat untuk membantu mengembangkan sistem penjualan secara online yang ada di Mechin Petshop. Perancangan sistem informasi ini memakai dua cara yaitu teknik pengumpulan data dengan metode wawancara, pengamatan, studi pustaka dan dokumentasi, untuk teknik pengembangan perangkat lunak dengan metode waterfall yaitu analisa kebutuhan perangkat lunak, desain, pembuatan kode program dan pengujian. Alat bantu yang pakai adalah ERD, LRS dan Struktur Navigasi. Pengujian website menggunakan Black Box Testing. Website yang telah dibuat diharapkan dapat memberikan kemudahan kepada konsumen untuk melakukan transaksi secara online 24 jam dan dari mana pun berada, diharapkan konsumen dapat melihat produk, bisa melakukan transaksi setiap saat, pelayanan lebih nyaman dan keuntungan bisa meningkat. Kata kunci : Informasi, Mechin Petshop, Penjualan Online